[18F]Fluorophenylazocarboxylates: Design and Synthesis of Potential Radioligands for Dopamine D3 and μ‑Opioid Receptor. - Nebel, Natascha; Strauch, Brigitte; Maschauer, Simone; Lasch, Roman; Rampp, Hannelore; Fehler, Stefanie; Bock, Leonard; Hübner, Harald; Gmeiner, Peter; Heinrich, Markus; Prante, Olaf (ACS Omega, 2017)
18F-Labeled building blocks from the type of [18F]fluorophenylazocarboxylic-tert-butyl esters offer a rapid, mild, and reliable method for the 18F-fluoroarylation of biomolecules. Two series of azocarboxamides were synthesized as potential radioligands for dopamine D3 and the μ-opioid receptor, revealing compounds 3d and 3e with single-digit and sub-nanomolar affinity for the D3 receptor and compound 4c with only micromolar affinity for the μ-opioid receptor, but enhanced selectivity for the μ-subtype in comparison to the lead compound AH-7921. A "minimalist procedure" without the use of a cryptand and base for the preparation of 4-[18F]fluorophenylazocarboxylic-tert-butyl ester [ 18 F]2a was established, together with the radiosynthesis of methyl-, methoxy-, and phenyl-substituted derivatives ([ 18 F]2b-f). With the substituted [18F]fluorophenylazocarbylates in hand, two prototype azocarboxylates radioligands were synthesized by 18F-fluoroarylation, namely the methoxy azocarboxamide [ 18 F]3d as the D3 receptor radioligand and [ 18 F]4a as a prototype structure of the μ-opioid receptor radioligand. By introducing the new series of [18F]fluorophenylazocarboxylic-tert-butyl esters, the method of 18F-fluoroarylation was significantly expanded, thereby demonstrating the versatility of 18F-labeled phenylazocarboxylates for the design of potential radiotracers for positron emission tomography .
EVALuna2:34730

Benzyl Phenylsemicarbazides: A Chemistry-Driven Approach Leading to G Protein-Biased Dopamine D4 Receptor Agonists with High Subtype Selectivity - Pirzer, Anna; Lasch, Roman; Friedrich, Heike; Hübner, Harald; Gmeiner, Peter; Heinrich, Markus (Journal of Medicinal Chemistry, 2019)
Many subtype-selective dopamine receptor ligands developed for the D2-D4 family incorporate a 1-arylpiperazine-derived primary recognition motif, which is connected to a lipophilic moiety occupying an extended binding pocket (EBP) of the receptor via an aliphatic linker of variable lengths. The evaluation of a novel group of dopamine receptor ligands now showed that highly subtype-selective ligands [up to Ki(D4.4) = 0.25 nM, D2L/D4.4 = 320, D3/D4.4 = 710 for APH199 (17)] can be obtained by choosing a relatively large and conformationally flexible 1-benzyl-1-phenylsemicarbazide substructure to fill the EBP. The novel chemotype APH199 (17) was found to act as a full agonist at the D4 receptor showing significant bias toward G protein activation over β-arrestin recruitment in comparison to quinpirole.
CRIS-Team Scopus Importer:2019-11-15

Cycloaddition reactions of glycine imine anions to phenylazocarboxylic esters - A new access to 1,3,5-trisubstituted 1,2,4-triazoles - Lasch, Roman; Heinrich, Markus (Tetrahedron, 2015)
Phenylazocarboxylic tert-butyl esters have recently been shown to be highly versatile building blocks due to their ability to undergo nucleophilic aromatic substitutions under mild conditions, particularly well with [18F]fluoride, and to act as precursors for aryl radicals. In this article, we now report first examples for cycloaddition reactions to phenylazocarboxylates. In a one-pot reaction with readily accessible glycine imines, a variety of highly substituted 1,2,4-triazoles could be obtained.
Keywords: 1; 2; 4-Triazoles; Azo compounds; Azocarboxylic esters; Cycloaddition; Glycine imines

Selective Functionalization of Graphene at Defect-Activated Sites by Arylazocarboxylic tert-Butyl Esters - Halbig, Christian E.; Lasch, Roman; Krüll, Jasmin; Pirzer, Anna; Wang, Zhenping; Kirchhof, Jan N.; Bolotin, Kirill I.; Heinrich, Markus; Eigler, Siegfried (Angewandte Chemie International Edition, 2019)
The development of versatile functionalization concepts for graphene is currently in the focus of research. Upon oxo-functionalization of graphite, the full surface of graphene becomes accessible for C-C bond formation to introduce out-of-plane functionality. Herein, we present the arylation of graphene with arylazocarboxylic tert-butyl esters, which generates aryl radicals after activation with an acid. Surprisingly, the degree of functionalization is related to the concentration of lattice vacancy defects in the graphene material. Consequently, graphene materials that are free from lattice defects are not reactive. The reaction can be applied to graphene dispersed in solvents and leads to bitopic functionalization as well as monotopic functionalization when the graphene is deposited on surfaces. As the arylazocarboxylic tert-butyl ester moiety can be attached to various molecules, the presented method paves the way to functional graphene derivatives, with the density of defects determining the degree of functionalization.
CRIS-Team WoS Importer:2019-03-20

Synthesis of 2-(Chlorodifluoromethyl)indoles for Nucleophilic Halogen Exchange with [18F]Fluoride - Bock, Leonard; Schultheiss, Stefanie K.; Maschauer, Simone; Lasch, Roman; Gradl, Susanne; Prante, Olaf; Zard, Samir Z.; Heinrich, Markus (European Journal of Organic Chemistry, 2021)
The synthesis of 2-[18F]trifluoromethylated indoles from the corresponding chlorodifluoromethyl precursors was found to proceed under milder conditions when compared to known metal-free nucleophilic exchange reactions with [18F]fluoride on chlorodifluoro-methyl arenes. A key element in the reaction course is – most likely – a favorable elimination-addition mechanism on the 2-methyl position of the indole. Given the increasing interest in 18F-labelled compounds, this single step labeling methodology nicely complements the so far existing routes to 2-[18F]trifluoromethylated indoles.
CRIS-Team Scopus Importer:2021-12-24
Keywords: Fluorine; Indoles; Nucleophilic substitution; Radical reactions; Radiochemistry